Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Kendaraan Roda 4 di Surabaya - Arvino Risqie Perdana Putra; Arga Christian Sitohang; Naufal Gama Affandyar (Nirta Learning Centre, 2024)
Abstract. The purpose of this study is to analyse the factors that influence the demand for 4-wheeled vehicles in Surabaya. This research uses descriptive quantitative methods. Sampling in this study using saturated sample technique. The sample selected for this study was 50 respondents. The results revealed that factors such as price, consumer tastes, and consumer income simultaneously have no influence on the demand for 4-wheeled vehicles in Surabaya. It is hoped that this information can be an input for the 4-wheeled vehicle manufacturing industry in Indonesia in determining labour specifications and technology. in determining the factors that can affect the demand for 4-wheeled vehicles, and can analyse the public's desire for the most desirable 4-wheeled vehicles.